Evaluation of Kinetic Mechanism for Modelling Dimethyl Ether Jet Diffusion Flame - Ahmad Syihan Auzani; Sheila Tobing; Ridhwan Sunandar; Riesta Anggarani; Cahyo Setyo Wibowo; Dedi Sutarma (Faculty of Engineering and Technology, Sampoerna University, 2022)
Many countries use liquefied petroleum gas (LPG) for various purposes, such as cooking and heating. As the population and the need for energy grow, demand for LPG steadily increases. This situation causes the rise in LPG imports for countries with an insufficient local supply, including Indonesia. To overcome this problem, the Indonesian Government plans to substitute LPG fuel with dimethyl ether (DME). However, stoves and household burners widely used in Indonesia are designed for LPG. Thus it is necessary to study the fuel flexibility of the burners. Many experimental studies on the substitution of LPG with DME are reported in the literature, but few models have been developed to simulate it. This paper aims to evaluate the performance of reaction mechanisms developed to model DME diffusion flames with various burner temperatures ranging from 300 to 1500 K. It was found that existing models could simulate the chemical structure of the flame but could not predict the formation of enthalpy of combustion reactions.